Efficient continuous kinetic resolution of racemic 2-aminobutanol over immobilized penicillin G acylase. Issue 11 (2nd June 2016) - Wang, Jianxin; Liu, Na; Cheng, Xiaobo; Chen, Ligong
ABSTRACT: In this paper, an efficient method was established for continuous kinetic resolution of racemic 2-aminobutanol by selective hydrolysis of N-phenylacetyl (±)-2-aminobutanol over immobilized penicillin G acylase (PGA) in a fixed-bed reactor. Several N-acylated derivatives of 2-aminobutanol were screened in batch experiments, and it was found that the hydrolysis of N-phenylacetyl (±)-2-aminobutanol proceeded smoothly in the presence of immobilized penicillin G acylase with satisfied enantioselectivity. Thus, the reaction parameters were optimized in a fixed-bed reactor. Under the optimized conditions, 39.3% conversion of N-phenylacetyl (±)-2-aminobutanol and 98.2% ee value of S-2-aminobutanol were obtained. This fixed-bed system was operated continuously for 40 h without significant decrease of enzyme activity. It has been demonstrated to be more efficient compared to the batch experiments. GRAPHICAL ABSTRACT: